Estimating the causal effect of frailty index on vestibular disorders: A two-sample Mendelian randomization - Xiao, Gui; Wang, Hu; Hu, Jiaji; Liu, Li; Zhang, Tingting; Zhou, Mengjia; Li, Xingxing; Qin, Chunxiang (Frontiers in Neuroscience, 2022)
Abstract Background Frailty index and vestibular disorders appear to be associated in observational studies, but the causality of the association remains unclear. Methods Two-sample Mendelian randomization (MR) study was implemented to explore the causal relationship between the frailty index and vestibular disorders. A genome-wide association study (GWAS) of frailty index was used as the exposure (n = 175, 226), whereas the GWAS of vestibular disorders was the outcome (n = 462,933). MR Steiger filtering method was conducted to investigate the causal effect of the frailty index on vestibular disorders. An inverse-variance weighted (IVW) approach was used as the essential approach to examine the causality. Additionally, the MR-Egger methods, the simple mode analysis, the weighted median analysis, and the weighted model analysis were used as supplementary methods. The MR-PRESSO analysis, the MR-Egger intercept analysis, and Cochran's Q statistical analysis also were used to detect the possible heterogeneity as well as directional pleiotropy. To evaluate this association, the odds ratio (OR) with 95% confidence intervals (CIs) was used. All statistical analyses were performed in R. The STROBE-MR checklist for the reporting of MR studies was used in this study. Results In total, 15 single nucleotide polymorphisms (SNPs) were identified as effective instrumental variables (IVs) in the two sample MR analyses. The significant causal effect of the frailty index on vestibular disorders was demonstrated by the IVW method [OR 1.008 (95% CI 1.003, 1.012), FDR-corrected p = 0.008]. Results from the various sensitivity analysis were consistent. The "leave-one-out" analysis indicated that our results were robust even without a single SNP. According to the MR-Egger intercept test [intercept =-0.000125, SE = 0.011, p = 0.608], genetic pleiotropy did not affect the results. No heterogeneity was detected by Cochran's Q test. Conclusion A causal relationship has been identified between genetically predicted frailty indexes and vestibular disorders according to our MR study. Accordingly, these results support the importance of effectively managing frailty in order to minimize vestibular disorders and improve the quality of life for those with vestibular disorders.